A produção de texto de opinião nas aulas de Língua Portuguesa: uma proposta de trabalho - Barbosa, Francisca Borges (2015)
In order to plan, apply and discuss a series of activities with the intent of contributing to the 9th grade student of Elementary School to be able to read, understand and write texts of opinion. In order to show how the proposal of working the genre as a tool can help students to be successful on the comprehension and production of text of opinion, we proposed a production of this type of writing from the perspective of interactional sociodiscursive Dolz, Noverraz and Schneuwly (2004) and didactic sequences. We also adopted the Bakhtinian assumptions, from that is possible to contemplate the three constitutive dimensions of genre (thematic content, compositional structure and style). To develop the proposal, we followed the planned steps by the didactic sequence. From that, the students were taken to the knowledge of the work object, the text of opinion; then, we propose the first production with diagnostic purposes. From the difficulties presented by the students in the first production, we prioritized in modules, activities that addressed the three elements of the genre, and finally, the final production work that was read by other students of the same school year that the participating students in the research. All the students productions were exposed on the school message board. The results showed that working with text of opinion in classroom, from the didactic sequence, helps students to obtain the writing competence. We noticed that in the course of initial production to final production, many students have built learning from the three constituents elements of the genre text of opinion, since many of them were able to stand by in relation to the proposed theme for the text productions that was dating without commitment - \"hook up\" and build argumentative strategies that supports their opinions. Besides, they have brought other voices to text built in the final production and appropriated themselves of the specific language of the genre being studied. Negative points were also noticed, both during the application of research and during data analysis. We found out, for example, that the time of the application of the methodological proposal was inadequate for a greater number of students could be able to achieve satisfactory results. Similarly, another point was considered, the large number of students who were participating in the activities affected the application of the research as it was planned.